Increased lipoxygenase and decreased cytochrome P450s metabolites correlated with the incidence of diabetic nephropathy: Potential role of eicosanoids from metabolomics in type 2 diabetic patients. (19th February 2021) - Peng, Liyuan; Sun, Bei; Liu, Yajin; Huang, Jing; Chen, Guangzhi; Zhang, Xu; Chen, Chen; Wang, Daowen; Wang, Gang
Abstract: Diabetic nephropathy (DN) is the major cause of chronic kidney disease and end‐stage renal disease. Previous studies have demonstrated that longchain omega3 polyunsaturated fatty acids (PUFAs) might have therapeutic potential in reducing proteinuria in DN. However, the local level of eicosanoids derived from PUFAs in the plasma of DN patients remains unclear. This work aims to study the eicosanoid profile difference in plasma of DN patients and type 2 diabetes (T2D) without DN. A total of 27 T2D patients with similar diabetic duration were recruited and divided into T2D+DN group and T2D+NDN (non‐DN) group based on urinary albumin excretion (UAE) detection. Using LC–MS/MS‐based metabolomics, DN patients showed increased level of lipoxygenase (LOX) metabolites (5‐HETE and LTB4) and decreased levels of eicosanoids derived according to the cytochrome P450s (CYP450) metabolic pathway (5, 6‐DHET; 14, 15‐DHET and 9, 10‐diHOME). Receiver operating characteristics and logistic regression analysis revealed increased level LOX metabolites and decreased level of CYP450 metabolites were significantly correlated with the incidence of DN in T2D patients. LOX and CYP450 metabolites correlated with DN incidence in T2D patients, which might be treatment targets for DN in T2D patients. Abstract : A targeted metabolomic method specific to eicosanoids was applied to study the profile of diabetic nephropathy (DN) and non‐DN patients. DN patients showed increased level of lipoxygenase (LOX) metabolites and decreased levels of eicosanoids derived according to the cytochrome P450s (CYP450) metabolic pathway.